Pengenalan Keragaman Budaya Suku Samin pada Siswa Ma'had As-Sultan Shah Addini Pahang Malaysia - Ali Mujahidin; Masnuatul Hawa; Zulfa Fauzul Muna; Putri Indah Tri Mawardani; Sherly Aisyia Anggraeni (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
Introduction to cultural diversity is an essential aspect in shaping an inclusive and tolerant understanding within society. One of the cultural groups worth studying is the Samin tribe, a community with a distinctive cultural heritage and unique traditions. The Samin tribe is known as an ethnic group rooted in classic Javanese traditions but with unique interpretations and spiritual values. This activity was attended by 60 second and third grade students from Ma'had As-Sultan Ahmad Shah Addini Pahang Malaysia, accompanied by 2 teachers. The outcomes of this activity can be seen from the pre- and post-activity evaluations. It can be concluded that the introduction to the cultural diversity and the Samin tribe to the students of Ma'had As-Sultan Ahmad Shah Addini Pahang Malaysia went well, as there was a change in knowledge before and after the introduction to the cultural diversity and the Samin tribe. Additionally, the enthusiasm of the participants was high, making this a significant factor in the success of this initiative.Keywords: Cultural diversity, Samin tribe, IndonesiaPengenalan terhadap keragaman budaya merupakan aspek penting dalam membentuk pemahaman yang inklusif dan toleran di dalam masyarakat. Salah satu kelompok budaya yang menarik untuk diteliti adalah suku Samin, sebuah komunitas yang memiliki warisan budaya khas dan tradisi unik. Suku Samin dikenal sebagai kelompok etnis yang memiliki akar budaya dalam tradisi Jawa klasik namun dengan interpretasi dan nilai-nilai spiritual yang khas. Kegiatan ini diikuti oleh 60 siswa dan siswi kelas 2 dan 3 dari Ma’had As-Sultan Ahmad Shah Addini Pahang Malaysia yang didampingi oleh 2 orang guru. Hasil dari kegiatan ini bisa dilihat dari evaluasi pra dan pasca kegiatan, maka bisa disimpulkan bahwa pengenalan keragaman budaya dan suku Samin pada siswa Ma’had As-Sultan Ahmad Shah Addini Pahang Malaysia berjalan dengan baik, karena ada perubahan pengetahuan sebelum adanya pengenalan dan setelah adanya pengenalan keragaman budaya dan suku Samin, selain dari pada itu antusiasme para peserta juga tinggi, sehingga ini juga termasuk salah satu faktor keberhasilan pengabdian ini. Kata Kunci: Keragaman budaya, Suku Samin, Indonesia